2011
DOI: 10.1111/j.1365-2672.2011.05091.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium species complex and mycotoxins in grain maize from maize hybrid trials and from grower’s fields

Abstract: Aims:  To quantify and to compare the occurrence of Fusarium species in maize kernels and stalk pieces, to analyse mycotoxins in kernels and maize crop residues, to evaluate two approaches to obtain kernel samples and to compare two methods for mycotoxin analyses. Methods and Results:  The occurrence of Fusarium species in maize kernels and stalk pieces from a three‐year maize hybrid trial and 12 kernel samples from grower’s fields was assessed. Nine to 16 different Fusarium species were detected in maize kern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 58 publications
(81 reference statements)
3
24
0
Order By: Relevance
“…This change may reflect a regional difference or a chemotype/species shift in recent years. Similar results were reported from Switzerland, where both dimensional and temporal variation of Fusarium composition on maize was observed (Dorn et al, 2009(Dorn et al, , 2011. Temporal variation events were also reported on wheat (Waalwijk et al, 2003;Ward et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…This change may reflect a regional difference or a chemotype/species shift in recent years. Similar results were reported from Switzerland, where both dimensional and temporal variation of Fusarium composition on maize was observed (Dorn et al, 2009(Dorn et al, , 2011. Temporal variation events were also reported on wheat (Waalwijk et al, 2003;Ward et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…Fusarium graminearum was prevalent in Yunnan province (southern China) from 1992 to 1995 (Li and Huang 1998). Dorn et al (2009Dorn et al ( , 2011 found that the distributions of Fusarium species could not be explained by temperature alone; it was suggested that temperature may not be critical and that other, yet unknown, factors more strongly influence Fusarium prevalence. Dowd and Johnson (2010) working in America, and Goertz et al (2010) in Germany, suggested that local field effects may influence both Fusarium outbreaks and maize mycotoxin levels more than do weather conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In other countries this pathogen has been found to survive in fields for years, e.g. in corn crop remnants it has survived for at least 3 years (Dorn et al, 2011). However, the survival of F. proliferatum in onion crop remnants has not been studied, and it is not known how persistent this species is in the field soil in Finland.…”
Section: Discussionmentioning
confidence: 99%